Kompetensi Pedagogik Tutor PAUD dalam Pelaksanaan Pembelajaran - Inayah, Aurora Nur; Aneza, Inka; Nursifah, Fitri; Yuliani, Lulu (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
Abstract. Pedagogic competence has an important role in the learning process. The purpose of this research is to understand the pedagogic abilities possessed by PAUD tutors at PAUD Syariatul Huda Tasikmalaya City and how these abilities affect the implementation of learning. The research method used in this study is descriptive qualitative, which aims to provide a detailed description of the situation and phenomena observed in PAUD Syariatul Huda. The subjects of this study were PAUD tutors, and to collect data the researcher used interviews, observation, and documentation. The findings from this study indicate that the academic qualifications of PAUD tutors can affect the tutor's abilities, knowledge, and understanding of students. The lack of pedagogical competence will also have an impact on the quality of the learning process for students. Until now, the learning carried out by tutors has not been able to reflect developments that cover all aspects of child development.